ATTITUDE AND KNOWLEDGE OF MEDICAL STUDENTS OF ISRA UNIVERSITY ABOUT DYSMENORRHOEA AND ITS TREATMENT - Parveen, Naheed; Majeed, Rehana; Zehra, Nishat; Rajar, Uzma; Munir, Aftab A (Journal of Ayub Medical College Abbottabad, 2009)
Background: Dysmenorrhoea is the term for painful menstruation. It is a common gynaecological complaint among female adolescent. The objective of this study was to assess attitude and knowledge about treatment of dysmenorrhoea among medical students of Isra University. Methods: This study was conducted at Isra University Hyderabad. Nonprobability, convenient random selection from MBBS student was done. Participants included were 18-25 years of ages, irrespective of marital status. Girls with irregular menstrual cycles, primary or secondary amenorrhea were excluded from the study. Pre-designed questionnaire was filled by the students. Results: A total of 197 female medical students were recruited, dysmenorrhoea was reported in 76%, of these 62.43% had primary and 13.19% had secondary dysmenorrhoea. Majority 89 (59.70%) of the girls had mild G1 to moderate 48 (32.21%) G2 dysmenorrhoea and twelve 8.05% were with sever dysmenorrhoea. The most common symptoms observed were abdominal cramps 94 (63%), irritability 91 (61.07%), headache 41 (24.5%) and vomiting 34 (22.8%). Different attitudes of students were assessed, that 40.6% of subjects can not do their routine work and 19.3% remain absent from education place. Only 69.5% students were using commercial pads, 67% girls were not taking bath and 92.4% were not doing exercise during menstruation, only 15 (7.6%) were doing exercise from the study population. Simple analgesic was the most known drug to 49.7% of participants for relief of dysmenorrhoea pain. Conclusion: Dysmenorrhoea is a common problem among young girls, and it significantly affects their class attendance, academic performance and routine work. Even being medical students, strong cultural believes were observed regarding menstrual cycle. Attitudinal changes are necessary to develop, educational strategies, appropriate use of medications and consultation with physician, to empower these young girls regarding healthy life-style. Keywords: dysmenorrhoea, medical students, associated symptoms, attitude, treatment